Transurethral resection and surveillance of a well-differentiated neuroendocrine tumor in a ileal neobladder - Audry Kang; Brittany Adamic; Caleb A. Cooper; Gladell P. Paner; Ryan P. Werntz (Urology Case Reports, 2020)
Our patient presented with a small, well-differentiated neuroendocrine tumor (NET) of the ileal neobladder 21-years after radical cystectomy for urothelial cell carcinoma. Given the rarity of NETs in urinary diversions, there are no established guidelines regarding management in this unique population. We propose that transurethral resection and close cystoscopic surveillance of the neobladder is a feasible, low morbidity approach to management of a well-differentiated, solitary ileal NET tumor.